2019
DOI: 10.5604/01.3001.0013.5526
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fragment Molecular Orbital Method to investigate dopamine receptors

Abstract: GPCRs are a vast family of seven-domain transmembrane proteins. This family includes dopamine receptors (D1, D2, D3, D4, and D5), which mediate the variety of dopamine-controlled physiological functions in the brain and periphery. Ligands of dopamine receptors are used for managing several neuropsychiatric disorders, including bipolar disorder, schizophrenia, anxiety, and Parkinson’s disease. Recent studies have revealed that dopamine receptors could be part of multiple signaling cascades, rather than of a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Interestingly, this correlates very well with the low values of the crystal temperature factors (B-factor) for atoms involved in the XB. In summary, the halogen bond with V5x40 is an important factor determining the binding mode of nemonapride with D 4 R. Moreover, the significance of this interaction was recently indicated based on the ab initio FMO calculation in combination with PIEDA analysis [34]. The study showed that XB between V5x40 and nemonapride is mostly dispersion-dependent, which was additional evidence of the hydrophobic nature of XBs.…”
Section: The 5wiu: MD Simulation Of the D 4 Receptor In Complex With mentioning
confidence: 83%
“…Interestingly, this correlates very well with the low values of the crystal temperature factors (B-factor) for atoms involved in the XB. In summary, the halogen bond with V5x40 is an important factor determining the binding mode of nemonapride with D 4 R. Moreover, the significance of this interaction was recently indicated based on the ab initio FMO calculation in combination with PIEDA analysis [34]. The study showed that XB between V5x40 and nemonapride is mostly dispersion-dependent, which was additional evidence of the hydrophobic nature of XBs.…”
Section: The 5wiu: MD Simulation Of the D 4 Receptor In Complex With mentioning
confidence: 83%
“…In FMO/PIEDA biomolecules, such proteins or nucleic acids are divided into substructures (fragments) and pair interaction energies (PIE) are calculated for such resulting individual fragments, making calculations more accurate than for whole large molecules [24][25][26]. The computational scheme proposed in this paper has been successfully applied previously to theoretical considerations of GPCR-targeted new drug design [27][28][29][30][31] as well as to deep insight into structure-activity relationship (SAR) analysis [32,33]. However, such a computationally comprehensive approach presented within this study has not been employed yet for D4R and the design of its ligands.…”
Section: Introductionmentioning
confidence: 99%